INTERNATIONAL EXPERIENCE IN DEVELOPING MANAGERIAL CAPABILITIES OF HIGHER EDUCATION ADMINISTRATIVE PERSONNEL (BASED ON THE EXAMPLES OF SINGAPORE AND FINLAND) - Rakhimov Mirvali Donayevich (Uzbekistan Open Conference, 2025)
In this article, the author comprehensively analyzes the experience of foreign universities in improving the managerial skills of higher education managers, including the Singaporean and Finnish higher education systems, as well as the effective management systems and methodological theories they employ. The article demonstrates that the methods and theories analyzed on this topic are effective tools for improving the managerial skills of managers in the Russian higher education system.
Keywords: Higher education; foreign experience; leadership programs; strategy; systematic approach; management; management theories; effective scientific method